Definition and the Epistemology of Natural Kinds in Aristotle. (21st May 2018) - Stein, Nathanael
We have reason to think that a fundamental goal of natural science, on Aristotle's view, is to discover the essence-specifying definitions of natural kinds—with biological species as perhaps the most obvious case. However, we have in the end precious little evidence regarding what an Aristotelian definition of the form of a natural kind would look like, and so Aristotle's view remains especially obscure precisely where it seems to be most applicable. I argue that if we can get a better understanding of how the forms of natural kinds are or come to be known, and how they make things intelligible, we can get a better appreciation of the nature of form in general, as well as solve certain puzzles about form and definition.